Assessing FinTech behavioral adoption to enhance financial readiness for retirement among Malaysian gig workers: A conceptual framework - Basar, Mohd Nur Fadzly; Sapuan, Noraina Mazuin; Osman, Azim Azuan (Journal of Islamic, Social, Economics and Development, 2026)
The rapid growth of gig economy has sparked worry about gig workers ability to retire with dignified financial wellbeing especially when employer-based benefits are absent and their incomes are inconsistent. Nowadays, financial technology (fintech) has become increasingly pertinent in financial management, offering everyone including gig workers new method to monitor their income, schedule automatic savings and to contribute voluntarily to their personal retirement fund. Yet, the studies about how their willingness to adopt fintech may influence their Financial Readiness for Retirement (FRR) are still limited. This paper proposes a conceptual framework that associates Fintech Behavioral Adoption (FBA) to FRR, grounded in the Net Valence Framework (NVF). In this model, FBA is shaped by how gig workers weigh the benefits of fintech such as easy to use, lower costs, and better financial oversight against the risks they associate with it, including privacy concerns and possible financial loss. When perceived benefits outweigh perceived risks, gig workers are more likely to adopt fintech to manage their finance and subsequently improve their FRR. The framework recommends a new insight for policymakers, financial institutions and platform providers seeking to design digital financial tools that useful for this vulnerable groups for preparing for their retirement age.